2017
DOI: 10.18632/oncotarget.19647
|View full text |Cite
|
Sign up to set email alerts
|

YAP1 is essential for tumor growth and is a potential therapeutic target for EGFR-dependent lung adenocarcinomas

Abstract: Epidermal growth factor receptor (EGFR) mutations are found in lung adenocarcinomas leading to tumor cells proliferation and survival. EGFR tyrosine kinase inhibitors (TKIs) that block EGFR activity are effective therapeutics for EGFR-mutant lung adenocarcinoma patients, but TKI-resistance inevitably occurs. The YES-associated protein (YAP1) transcription coactivator has been implicated as an oncogene and is amplified in human cancers and provides tumor cells strong proliferation and survival cues. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
1
13
0
1
Order By: Relevance
“…In NSCLC patients, TEAD activity correlates with the EGFR mutation status. EGFR mutant lung cancer tissues and cell lines show upregulated YAP expression, followed by increased TEAD activity [165]. Although EGFR acquires drug resistance to TKI via the T790M mutation, TEAD inhibition effectively reduces the viability of TKI-resistant lung adenocarcinoma cells [166,167].…”
Section: Teads As Mediators Of Cancer Genesmentioning
confidence: 99%
“…In NSCLC patients, TEAD activity correlates with the EGFR mutation status. EGFR mutant lung cancer tissues and cell lines show upregulated YAP expression, followed by increased TEAD activity [165]. Although EGFR acquires drug resistance to TKI via the T790M mutation, TEAD inhibition effectively reduces the viability of TKI-resistant lung adenocarcinoma cells [166,167].…”
Section: Teads As Mediators Of Cancer Genesmentioning
confidence: 99%
“…Likewise, Epidermal Growth Factor Receptor (EGFR) signaling, which is altered in many cancers, regulates YAP/TAZ activity. EGFR-mediated regulation of the Hippo pathway was first described in Drosophila [ 336 ], and subsequent studies showed that EGFR activation inhibits the Hippo pathway to promote YAP/TAZ activity [ 337 , 338 , 339 ]. Importantly, EGFR-mediated YAP/TAZ activity can drive cancer development and progression [ 105 , 338 , 339 , 340 , 341 ].…”
Section: Therapeutic Potential Of Targeting Yap/taz-tead In Cancermentioning
confidence: 99%
“…EGFR-mediated regulation of the Hippo pathway was first described in Drosophila [ 336 ], and subsequent studies showed that EGFR activation inhibits the Hippo pathway to promote YAP/TAZ activity [ 337 , 338 , 339 ]. Importantly, EGFR-mediated YAP/TAZ activity can drive cancer development and progression [ 105 , 338 , 339 , 340 , 341 ]. In addition, studies also show that YAP/TAZ activation is a mechanism of resistance to EGFR inhibitors [ 97 , 342 , 343 , 344 , 345 ].…”
Section: Therapeutic Potential Of Targeting Yap/taz-tead In Cancermentioning
confidence: 99%
“…Therefore, the combination of YAP1 knockdown and administration of sorafenib could exert a stronger inhibitory effect on tumor progression compared with YAP1 knockdown or sorafenib alone. 38 , 39 …”
Section: Discussionmentioning
confidence: 99%